Possibilities of optical fluorescence spectral decomposition of meibum - Safonova, T N; Novikov, I A; Zaitseva, G V; Dobretsova, E A; Solodovnikov, V I (Vestnik oftal'mologii, 2025)
The is study evaluated the possibilities of using optical fluorescence to determine the components of meibum. Meibum samples from 16 volunteers were analyzed using fluorescence spectroscopy in the visible optical range. The meibum spectrum was decomposed into three spectral components corresponding to the fluorescence of three reference substances: native keratin, lactoferrin, and riboflavin-mononucleotide. Each meibum sample was characterized by the spectral fraction of each of the three dominant fluorophores. The meibum spectra of 16 studied samples were obtained by fluorescence spectroscopy in the visible optical range under 440 nm laser excitation. Fluorescence of the meibum sample was detected in all cases. Using the proposed algorithm, the relative spectral component of one of the proposed reference substances was calculated for each real spectrum. Fluorescence spectroscopy in the visible optical range, alongside other methods, allows the identification of major compartments constituting the bulk of meibum mass.